2016 SCCT/STR guidelines for coronary artery calcium scoring of noncontrast noncardiac chest CT scans: A report of the Society of Cardiovascular Computed Tomography and Society of Thoracic Radiology. Issue 5 (September 2017) - Hecht, Harvey S.; Cronin, Paul; Blaha, Michael J.; Budoff, Matthew J.; Kazerooni, Ella A.; Narula, Jagat; Yankelevitz, David; Abbara, Suhny
Abstract : The Society of Cardiovascular Computed Tomography (SCCT) and the Society of Thoracic Radiology (STR) have jointly produced this document. Experts in this subject have been selected from both organizations to examine subject-speciﬁc data and write this guideline in partnership. A formal literature review, weighing the strength of evidence has been performed. When available, information from studies on cost was considered. Computed tomography (CT) acquisition, CAC scoring methodologies and clinical outcomes are the primary basis for the recommendations in this guideline. This guideline is intended to assist healthcare providers in clinical decision making. The recommendations reﬂect a consensus after a thorough review of the best available current scientiﬁc evidence and practice patterns of experts in the ﬁeld and are intended to improve patient care while acknowledging that situations arise where additional information may be needed to better inform patient care.